Synthetic Crystals of Silver with Carbon: 3D Epitaxy of Carbon Nanostructures in the Silver Lattice. (2nd July 2015) - Salamanca‐Riba, Lourdes G.; Isaacs, Romaine A.; LeMieux, Melburne C.; Wan, Jiayu; Gaskell, Karen; Jiang, Yeping; Wuttig, Manfred; Mansour, Azzam N.; Rashkeev, Sergey N.; Kuklja, Maija M.; Zavalij, Peter Y.; Santiago, Jaime R.; et al.
Abstract : Only minimum amounts of carbon can be incorporated into silver, gold, and copper in a thermodynamically stable form. Here, the structure of stable silver carbon alloys is described, which are produced by thermoelectrically charging molten silver with carbon ions. Transmission electron microscopy and Raman scattering are combined to establish that large amount of carbon is accommodated in the form of epitaxial graphene‐like sheets. The carbon bonds covalently to the silver matrix as predicted from density functional theory (DFT) calculations with bond energies in the range 1.1–2.2 eV per atom or vacancy. Graphitic‐like sheets embedded in the crystal lattice of silver form 3D epitaxial structures with the host metal with a strain of ≈13% compared to equilibrium graphene. The carbon nanostructures persist upon remelting and resolidification. A DFT‐based analysis of the phonon density of states confirms the presence of intense vibration modes related to the AgC bonds observed in the Raman spectra of the alloy. The solid silver–high carbon alloy, termed "Ag‐covetic, " displays room temperature electrical conductivity of 5.62 × 10 7 S m −1 even for carbon concentrations of up to ≈6 wt% (36 at%). This process of incorporation of carbon presents a new paradigm for electrocharging assisted bulk processing. Abstract : Incorporation of C in the lattice of silver is produced by electrocharging assisted bulk processing to create a synthetic alloy called silver covetic. In some regions the carbon forms layers of graphene intercalated between the atomic planes of silver forming a 3D nanoepitaxial structure. Carbon and silver atoms bond at carbon vacancies and edges of graphene‐like sheets or ribbons.